1996
DOI: 10.1111/j.1432-1033.1996.00465.x
|View full text |Cite
|
Sign up to set email alerts
|

Mutations of Glu92 in Ferredoxin I from Spinach Leaves Produce Proteins Fully Functional in Electron Transfer but Less Efficient in Supporting NADP+ Photoreduction

Abstract: Ferredoxin I in spinach chloroplasts fulfils the role of distributing electrons of low redox potential produced by photosystem I to several metabolic routes, NADP' reduction being the major output. To investigate the role of Glu92, which is conserved in the chloroplast-type ferredoxins, mutations of this residue to either Gln, Ala or Lys were obtained through site-directed mutagenesis. A Glu93Ala mutant was also designed. The four mutants of ferredoxin I were overproduced in Escherichia coli, purified and char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
1

Year Published

1997
1997
2004
2004

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 22 publications
2
23
1
Order By: Relevance
“…Our results strongly suggest that in the C terminus, only residue Glu-9l (E92 in spinach) is essential for this interaction. The results obtained in the present study also fit very well with the data of [8] where mutations of the E92 residue of spinach ferredoxin was found to increase its reactivity with FNR in the cytochrome c reduction assay. On the other hand, the triple mutant in the al helix is completely inactive in the NADP-MDH light activation assay, a feature which was not expected from the results in [10].…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…Our results strongly suggest that in the C terminus, only residue Glu-9l (E92 in spinach) is essential for this interaction. The results obtained in the present study also fit very well with the data of [8] where mutations of the E92 residue of spinach ferredoxin was found to increase its reactivity with FNR in the cytochrome c reduction assay. On the other hand, the triple mutant in the al helix is completely inactive in the NADP-MDH light activation assay, a feature which was not expected from the results in [10].…”
Section: Resultssupporting
confidence: 80%
“…On the other hand, the Glu-91 mutants of Chlamydomonas reinhardtii are indeed reduced by PSI since the (E91K) mutant supports NADP photoreduction, albeit at a reduced rate (ca. 50%, data not shown), in a similar manner to the corresponding (E92K) mutant of spinach [8]. It is highly unlikely that the incapacity of the Glu-91 mutants to promote the NADP-MDH activation results from the poorer interaction with PSI since the process of enzyme light activation requires a much lower electron flow than NADP photoreduction [21].…”
Section: Resultssupporting
confidence: 48%
See 1 more Smart Citation
“…strain PCC 7119 and spinach and found that electrostatic interactions most likely contributed to the formation of protein complex that permits electron transfer. Furthermore, it has been determined that alterations at specific positions (E92) in spinach ferredoxin could increase activity of ferredoxin in supporting NADPH/FNR mediated cyt C reduction and reduced the activity of ferredoxin in supporting photoreduction of NADP ϩ by photosystem I (Piubelli et al, 1996). These studies collectively show it is possible to alter kinetic activity without significantly altering redox potential.…”
Section: Discussionmentioning
confidence: 61%
“…Redox potential of Anabaena sp. ferredoxin has been determined to be Ϫ440 mV (Hurley et al, 1993), whereas the major leaf isoform (Fd I) in spinach has a redox potential measured at Ϫ400 mV (Aliverti et al, 1995;Piubelli et al, 1996). Since NADPH/NADP ϩ redox potential is Ϫ320 mV the transfer of electrons from NADPH to the Anabaena sp.…”
Section: Discussionmentioning
confidence: 99%